Implementasi Pemahaman Konsumsi Islam Pada Perilaku Konsumsi Konsumen Muslim - Zulfikar Alkautsar; Meri Indri Hapsari (Universitas Airlangga, 2014)
People does consumption to fulfill their needs in order to keeping their life. There are guidelines in Islam telling how a Moslem is supposed to consumed. A Moslem needs a comprehensive understanding about Islamic consumption in order to adjust their consuming behaviour with Islamic syaria. The understanding causes an implication of Moslem consumer behaviour in daily life.This research uses case study method with descripive qualitative approach. Author uses interview for primary data collection in this research. The scope of this research is limited in student of Islamic Economics of Economics and Business Faculty of Airlangga University and answer how to implement Islamic consumption understanding in Moslem consumption behavior.The result of this research shows there are four elements of Islamic consumption which is used as a guideline for moslem while they do consumption, ie: halal products consumption, avoiding excessive consumption (israf), paying zakat, infaq, and charity, and making needs priority. The informen confess that there is a difference in their consuming behaviour beforeand after knowing the Islamic consumption theory. REFERENCES Badan Pusat Statistik. 2013. Perkembangan Beberapa Indikator Utama SosialEkonomi Indonesia. Jakarta: Badan Pusat Statistik, (Online). (http://www.bps.go.id/aboutus.ph p?booklet=1, diakses pada 10 Maret 2014).Badudu, J.S. (2003) Kamus Kata-kata Serapan Asing Dalam Bahasa Indonesia, Jakarta : Kompas.Belch, George E. dan Michael A. Belch. 2003. Advertising and Promotion (An Integrated Communications Perspective 6th Edition. New York: Mc Graw Hill Companies.Bereiter, Carl. 2000. Education and Mind in the Knowledge Age. New Jersey: John Wiley And Sons LTD. Departemen Agama Republik Indonesia.2005.Al-Qur’an Terjemahan. Jakarta: PT. Syamil Cipta Media.Hidayat, mohammad. 2010. An Introduction to the Sharia Economics. Jakarta: Zikrul Hakim.http://repository.usu.ac.id/bitstream/12345 6789/14510/1/10E00397.pdf, diakses pada 15 Maret 2014).http://www.setneg.go.id/index.php?optio n=com_content&task=view&id=706 8, diakses pada 4 Maret 2014 Katsir, Ibnu. 2000. Tafsir Ibnu Katsir. Bandung. Sinar Baru Algensindo.Kushendrawati, Selu Margaretha. 2006. Masyarakat Konsumen Sebagai Ciptaan Kapitalisme Global: Fenomena Budaya Dalam Realitas Sosial, (Online), Vol. 10, No. 2, (http://journal.ui.ac.id/index.php/h umanities/article/viewFile/19/15, diakses pada 17 April 2014).Mayasari, Iin & Anita Maharani. 2011. Idealisme versus Relativisme Generasi Y Terhadap Iklan dengan Tema Sexual Appeal. Karisma. V (2): 84-93.Muflih, Muhammad. 2006. Perilaku Konsumen Dalam Prespektif Ilmu Ekonomi Islami. Jakarta: RajaGrafindo Persada.Myers, David G. 2010. Social Psychology 10th Edition. New York: Mc Graw Hill.Nurist, Surayya. 2010. Posmodernisme dan Budaya Konsumen, (Online), (http://eprints.undip.ac.id/9820/, diakses 10 April 2014).Partowisastro, Koestoer. 1983. Dinamika Dalam Psikologi Pendidikan (Jilid I). Jakarta: Erlangga.Piliang, Yasraf Amir. 2004. Dunia Yang Dilipat: Tamasya Melalui BatasBatas Kebudayaan. Bandung: Jalasutra.Poerwadarminta, W.J.S.1976. Kamus Umum Bahasa Indonesia. Jakarta : Balai Pustaka.Pujiyono, Arif. 2006. Teori Konsumsi Islam. Jurnal Dinamika Pembangunan. III (2): 196-207. Pusat Pengkajian dan Pengembangan Ekonomi Islam (P3EI), 2011. Ekonomi Islam. Jakarta:Rajawali Pers.Shihab, M. Quraish. Tafsir al-Mishbah; Pesan, Kesan, dan Keserasian alQur’an. Jakarta; Lentera Hati. 2003.Sholihin, Ahmad Ifham. 2010. Buku Pintar Ekonomi Syariah. Jakarta: Gramedia Pustaka Utama.Simbolon, Hotpascaman. 2010. Hubungan Antara Perilaku Konsumtif Dengan Konformitas Pada Remaja. Skripsi diterbitkan. Medan Universitas Sumatera Utara. (Online).Sudjana, Nana. 2010. Evaluasi Proses Dan Hasil Pembelajaran. Jakarta: Bumi Aksara.Sugiyono. 2012. Metode Penelitian Kuantitatif, Kualitatif Dan R&D.Bandung: Alfabeta.Sumartono. 2002. Terperangkap Dalam Iklan (Meneropong Imbas Pesan Iklan Televisi). Bandung: Alfabeta.Wigati, Sri. 2011. Perilaku Konsumen Dalam Prespektif Ekonomi Islam. Jurnal Maliyah, (Online), Vol 1, No.1, (http:// portalgaruda.org/?ref=browse&mo d=viewarticle&article=88351, diakses 15 Maret 2014).Yin, Robert K. 2009. Case Study Research 4th Edition. California: SAGE Inc.